Back Cover: Optimizing Acetylene Sorption through Induced‐fit Transformations in a Chemically Stable Microporous Framework (Angew. Chem. Int. Ed. 7/2023). Issue 7 (19th January 2023) - Tian, Jinduo; Chen, Qihui; Jiang, Feilong; Yuan, Daqiang; Hong, Maochun
Abstract : Optimizing acetylene (C2 H2 ) sorption through induced‐fit transformations of a metal–organic framework has been achieved. In their Research Article (e202215253), Qihui Chen, Daqiang Yuan, Maochun Hong, and co‐workers describe the preparation of an adaptive ultramicroporous framework that effectively captures C2 H2 with a record‐high storage density but a very low adsorption enthalpy. Mechanistic studies demonstrate that the excellent adsorption performance is due to the synergism of active sites, a flexible framework, and matched pores.